A 3-axis torsion quasi-zero-stiffness-based sensor system for angular vibration measurement. (September 2018) - Tuo, Jiying; Deng, Zhaoxiang; Zhang, Heshan; Qiu, Jinshan
In this paper, a novel 3-axis torsion quasi-zero-stiffness (TQZS)-based sensor system is proposed for absolute rotation measurement in vibration systems. Analysis on the applied torque and structural parameters shows that the proposed mechanism with two concentric spheres connected by six symmetry distributed springs could approximately achieve TQZS features in three rotational degrees of freedom simultaneously, thus a remarkable torsional vibration measurement performance can be guaranteed. Although due to high stiffness, the mechanism also has high anti-interference ability about force or vibration in translational directions. Mathematical modeling and numerical simulations are carried out to show the effectiveness of the proposed 3-axis sensor system in different base vibrations. In consideration of its feasibility and high performance, it can be foreseen that the proposed TQZS-based sensor will get more and more implementations in various engineering practices with torsional vibration measurements.